Maximum shear modulus and modulus degradation curves of an unsaturated tropical soil - Fernandes, Jeferson Brito [UNESP]; Rocha, Breno Padovezi; Giacheti, Heraldo Luiz [UNESP] (Associação Brasileira de Mecânica dos Solos, 2023)
The maximum shear modulus (G0) and the modulus degradation curve (G/G0 versus γ) are important information in the evaluation of the soil mechanical behavior, both for dynamic and static loads. Dynamic tests (resonant column and cyclic triaxial tests) are not routinely performed in geotechnical practice in Brazil, and the geotechnical literature on the dynamic behavior of unsaturated tropical soils is limited. This paper presents and discusses seismic dilatometer (SDMT), resonant column, and triaxial test with bender elements and internal instrumentation to determine G0 and the modulus degradation curve in an unsaturated tropical sandy soil profile. It was observed that G0 tends to increase non-linearly with soil suction and net stress (σ - ua). It was also observed that the in situ G0 values determined with the SDMT were higher than those from laboratory tests (bender elements and resonant column). The modulus degradation curves determined with resonant column were used to define the reference curve via SDMT for the studied site. Soil suction influence in shear modulus degradation curves determined with unsaturated triaxial compression tests with local instrumentation is also presented and discussed.
Keywords: Maximum shear modulus; Modulus degradation; Triaxial test; Bender elements; SDMT; Soil suction